2014
DOI: 10.4314/ajtcam.v11i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive activity of methanol extract of <i>Melastoma malabathricum</i> leaves in DMBA-induced mouse skin carcinogenesis

Abstract: Background: Melastoma malabathricum L. Smith (family Melastomaceae) is a shrub that has been used by the Malay practitioners of traditional medicine to treat various types of ailments. The present study aimed to determine the chemopreventive activity of methanol extract of M. malabathricum leaves (MEMM) using the standard 7,12-dimethylbenz(α)anthracene (DMBA)/croton oil-induced mouse skin carcinogenesis model. Materials and Methods:In the initiation phase, the mice received a single dose of 100µl/100 µg DMBA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…55 However, the matK region has not been considered ideal in many plant groups due to its low PCR success rate and sequencing. 56 Molecular identification of T. govanianum by developing DNA barcode sequences is available in some studies. 57, 58 Osaloo and Kawano 57 observed less resolution in the rbcL marker-based tree in the phylogenetic analysis of Trillium and other allied species.…”
Section: Discussionmentioning
confidence: 99%
“…55 However, the matK region has not been considered ideal in many plant groups due to its low PCR success rate and sequencing. 56 Molecular identification of T. govanianum by developing DNA barcode sequences is available in some studies. 57, 58 Osaloo and Kawano 57 observed less resolution in the rbcL marker-based tree in the phylogenetic analysis of Trillium and other allied species.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the methanol extract of M. malabathricum leaves (MEMM), pharmacological activities such as antiproliferative, antioxidant and antiulcer have been cited by Joffry et al (2012). After 2012, several new studies have demonstrated the potential of M. malabathrium to exert antioxidant and hepatoprotective (Mamat et al, 2013), antidiabetic, antioxidant and anti-hyperlipidemic (Kumar et al, 2013), chemopreventive (Kooi et al, 2014), anticoagulant (Khoo et al, 2014), gastroprotective (Zakaria et al, 2015), anti-obesity (Karupiah & Ismail, 2015), antinociceptive (Jaios et al, 2016), anti-inflammation (Kumar et al, 2016), and chemomodulatory (Verma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%